Abuse potential of intranasal buprenorphine versus buprenorphine/naloxone in buprenorphine‐maintained heroin users. (25th July 2014) - Jones, Jermaine D.; Sullivan, Maria A.; Vosburg, Suzanne K.; Manubay, Jeanne M.; Mogali, Shanthi; Metz, Verena; Comer, Sandra D.
Abstract In spite of the clinical utility of buprenorphine, parenteral abuse of this medication has been reported in several laboratory investigations and in the real world. Studies have demonstrated lower abuse liability of the buprenorphine/naloxone combination relative to buprenorphine alone. However, clinical research has not yet examined the utility of the combined formulation to deter intranasal use in a buprenorphine‐maintained population. Heroin‐using volunteers (n = 12) lived in the hospital for 8–9 weeks and were maintained on each of three sublingual buprenorphine doses (2, 8, 24 mg). Under each maintenance dose, participants completed laboratory sessions during which the reinforcing and subjective effects of intranasal doses of buprenorphine (8, 16 mg), buprenorphine/naloxone (8/2, 8/8, 8/16, 16/4 mg) and controls (placebo, heroin 100 mg, naloxone 4 mg) were assessed. Intranasal buprenorphine alone typically produced increases in positive subjective effects and the 8 mg dose was self‐administered above the level of placebo. The addition of naloxone dose dependently reduced positive subjective effects and increased aversive effects. No buprenorphine/naloxone combination dose was self‐administered significantly more than placebo. These data suggest that within a buprenorphine‐dependent population, intranasal buprenorphine/naloxone has reduced abuse potential in comparison to buprenorphine alone. These data strongly argue in favor of buprenorphine/naloxone rather than buprenorphine alone as the more reasonable option for managing the risk of buprenorphine misuse.